2011
DOI: 10.1002/agr.20285
|View full text |Cite
|
Sign up to set email alerts
|

Do Health Claims and Prior Awareness Influence Consumers' Preferences for Unhealthy Foods? The Case of Functional Children's Snacks

Abstract: This study investigates if and how the translation of different types of functionality into measurable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Online choice experiment.173 primary food shoppers and consumers of yogurt.Random parameter logit with an error component model. De-Magistris (2016) [36]Spain.Repeated measures: price (4 levels) x nutrient claim (absent, reduced fat claim, low salt claim). Setting unclear, conducted in-person, participants seated individually.217 primary food shoppers.Random Parameters Logit (RPL) model. Fernández-Polanco (2013) [37]Spain.Repeated measures: price (4 levels) x origin (2 levels) x harvest method (2 levels) x sustainability (2 levels) x health claim (2 levels) x safety (2 levels).169 participants.Heteroscedastic logit model. Gracia (2009) [38]Spain.Repeated measures: price (2 levels) x brand (2 levels) x nutritional information panel (2 levels x claim (2 levels).400 food shoppers.Logit model. Krystallis (2012) [42]Greece.Repeated measures: product type (2 levels) x claims (5 levels) x flavour (2 levels) x price (3 levels).140 participants.Heteroscedastic extreme value (HEV) model. Van Wezemael (2014) [54]Belgium, France, the Netherlands, and the UK.Mixed design: between groups (nutrition or health & nutrition claim exposure), within group (claim, no claim) x price (4 levels). Conducted online.2400 beef consumers, 600 participants from; the Netherlands, Belgium, France, and the UK.Multinomial logit (MNL) model, error component (EC) logit model. Ares (2010) [27]Uruguay.Repeated measures: type of yogurt (3 levels) x brand (3 levels) x price (3 levels) x claim (with/without).104 yogurt consumers.Multinomial logit model (MNL).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Online choice experiment.173 primary food shoppers and consumers of yogurt.Random parameter logit with an error component model. De-Magistris (2016) [36]Spain.Repeated measures: price (4 levels) x nutrient claim (absent, reduced fat claim, low salt claim). Setting unclear, conducted in-person, participants seated individually.217 primary food shoppers.Random Parameters Logit (RPL) model. Fernández-Polanco (2013) [37]Spain.Repeated measures: price (4 levels) x origin (2 levels) x harvest method (2 levels) x sustainability (2 levels) x health claim (2 levels) x safety (2 levels).169 participants.Heteroscedastic logit model. Gracia (2009) [38]Spain.Repeated measures: price (2 levels) x brand (2 levels) x nutritional information panel (2 levels x claim (2 levels).400 food shoppers.Logit model. Krystallis (2012) [42]Greece.Repeated measures: product type (2 levels) x claims (5 levels) x flavour (2 levels) x price (3 levels).140 participants.Heteroscedastic extreme value (HEV) model. Van Wezemael (2014) [54]Belgium, France, the Netherlands, and the UK.Mixed design: between groups (nutrition or health & nutrition claim exposure), within group (claim, no claim) x price (4 levels). Conducted online.2400 beef consumers, 600 participants from; the Netherlands, Belgium, France, and the UK.Multinomial logit (MNL) model, error component (EC) logit model. Ares (2010) [27]Uruguay.Repeated measures: type of yogurt (3 levels) x brand (3 levels) x price (3 levels) x claim (with/without).104 yogurt consumers.Multinomial logit model (MNL).…”
Section: Resultsmentioning
confidence: 99%
“…There was one study that measured the effects of health-related claims on ‘Fruits and Vegetables’ [48] whereas there were nine studies that examined ‘Foods High in Fat and/or Sugar’ [26, 31, 33, 35, 3840, 42, 53], five studies examined ‘Beans, Pulses, Fish, Eggs, Meat and other Proteins’ [37, 44, 47, 50, 54], three studies on ‘Potatoes, Bread, Rice, Pasta and Other Starchy Carbohydrates’ [34, 46, 52], four studies on ‘Dairy and Alternatives’ [27, 36, 45, 51], and two studied ready meals [32, 41]. Six studies looked at multiple categories of foods [14, 25, 2830, 49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Bech‐Larsen and Grunert () suggest that, beyond health claims, also the type of base product has a great impact on consumers’ trust in the healthiness of FFs. Moreover, Kristallis and Chrysochou () found that the type of food that ‘‘carries’’ functionality was even more important when consumers had no knowledge of functionality. In this regard, also the current findings show that parents’ willingness to buy FFs for children is higher for products with a healthy carrier.…”
Section: Discussionmentioning
confidence: 99%
“…With specific reference to FFs, according to Krystallis and Chrysochou (2012), parents generally perceive functionality as a product attribute that contributes positively to FF image enhancement and stated they were willing to pay reasonable premiums for it. However, despite the extensive literature on FF foods, few papers currently focus on FFs targeting children or provide empirical evidence from parents (Krystallis and Chrysochou, 2012).…”
Section: Introductionmentioning
confidence: 99%